2021
DOI: 10.3389/fgene.2021.665344
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Prediction of Average Daily Gain, Back-Fat Thickness, and Loin Muscle Depth Using Different Genomic Tools in Canadian Swine Populations

Abstract: Improvement of prediction accuracy of estimated breeding values (EBVs) can lead to increased profitability for swine breeding companies. This study was performed to compare the accuracy of different popular genomic prediction methods and traditional best linear unbiased prediction (BLUP) for future performance of back-fat thickness (BFT), average daily gain (ADG), and loin muscle depth (LMD) in Canadian Duroc, Landrace, and Yorkshire swine breeds. In this study, 17,019 pigs were genotyped using Illumina 60K an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Ardestani et al (2021) [3] proved the superiority of genomic methods for predicting breeding value over the traditional BLUP procedure in Duroc, Landrace and Yorkshire pigs for meat traits. The greatest estimate reliability for fat thickness, muscle depth and average daily gain was achieved by ssGBLUP and BayesCp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ardestani et al (2021) [3] proved the superiority of genomic methods for predicting breeding value over the traditional BLUP procedure in Duroc, Landrace and Yorkshire pigs for meat traits. The greatest estimate reliability for fat thickness, muscle depth and average daily gain was achieved by ssGBLUP and BayesCp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase in reliability was different for each breed studied. According to the authors, this occurrence can be caused by differences in the reference group's volume, the amount of data available for evaluation, and the differences in the breeding selection goals [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single nucleotide polymorphism (SNP) arrays can genotype hundreds of thousands of SNPs distributed throughout the genome ( 11 ). Based on the density, the porcine SNP arrays were split into 50K ( 12 ), 60K ( 13 ), and 80K ( 14 ). The beadchips have been widely used for genomic selection ( 15 ), selection signature research ( 14 ), and genome-wide association studies ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the livestock industry, genomic selection for productive traits is used to rapidly improve livestock. Genomic prediction studies for the ADG trait have been extensively conducted in different pig populations [ 11 , 15 , 16 , 17 , 18 ]. Genomic selection events in purebred pigs have been suggested to increase the selection response for performance in crossbred pigs [ 19 ], and Ask et al [ 11 ] have recently shown that selection for the SGE on ADG in purebred pigs can improve ADG in two-way crossbred pigs.…”
Section: Introductionmentioning
confidence: 99%